ANALISIS MANAJEMEN PEMERINTAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH MELALUI SEKTOR PARIWISATA “WISATA KERENG BANGKIRAI KOTA PALANGKA RAYA KALIMANTAN TENGAH”: (Studi di Dinas Kebudayaan dan Pariwisata Kota Palangka Raya) - Wijoko Lestariono; Penny Yuliansari (Jurusan Ilmu Pemerintahan, 2021)
National Development in Indonesia by developing regions through the development of existing potential, one of the regional potentials that can be developed is the tourism sector where this activity plays a very important role in supporting the economy both centrally and regionally. Tourism activities can contribute to regional revenues sourced from regional levies through purchasing entrance tickets at tourist sites, based on data from the Culture and Tourism Office of the City of Palangka Raya in 2020. Total PAD from the tourism sector is around 406,283,200 by having 34 tourist destinations with various kinds. Tourist attractions include natural, artificial, religious and cultural tourism. One of the attractions in the city of Palangka Raya is the Kereng Bangkirai Pier tour, which is unique, namely the black water This study aims to determine and analyze government management in increasing Regional Original Income through tourism development, Kereng Bangkirai Pier Tourism in Palangka Raya City, Central Kalimantan. Using the theory of Managing Government, Governing Management (Hendry Mitntzberg), in analyzing and reviewing 4 programs of the Department of Tourism, namely, tourism marketing development programs, tourism destination development programs, partnership development programs, cultural wealth development and management programs. The method used is qualitative research, with data collection techniques through an interview process, namely the Department of Culture and Tourism, as well as business actors around the Kereng Bangkirai Pier Tourism area. Based on the data found, the results of this study indicate that 4 programs from the Tourism Office using the theory of Managing Government, Governing Management (Hendry Mitntzberg) have been implemented and the Kereng Bangkirai Pier tourism is one of the contributors to PAD for the City of Palangka Raya, suggestions that can be given from this research Both the government and the actors in the Kereng Bangkirai Pier Tourism sector can continue to optimize tourism both from natural resources and human resources to attract tourists every year so that PAD will increase.